Radiation survey of the territory of the Republic of Belarus adjacent to Ignalina NPP - Bugrov, Юрий Александрович; Nilova, Екатерина Константиновна; Kronova, Жанна Геннадьевна; Samsonov, Владимир Леонидович (Journal of Civil Protection, 2022)
Purpose. To carry out a selective survey of the territory of the Republic of Belarus adjacent to the area where the Ignalina NPP is located. Methods. Gamma spectrometric method, comparative analysis, expert evaluation method. Findings. The article presents the results of measurements of the main parameters characterizing the radiation situation on the territory of the Belarusian segment of the observation zone of the Ignalina NPP – values of the ambient dose equivalent rate of γ-radiation and the total count rate of γ-radiation pulses, carrying out γ-spectrometry in the field using scintillation and semiconductor spectrometers, as well as determining the volumetric activity of radionuclides present in the surface layer of atmospheric air, the specific activity of radionuclides in samples of soil, water and bottom sediments. As a result of processing the spectra in environmental objects in the survey area, the presence of terrigenous radioisotopes (40K, daughter members of the 232Th and 226Ra (238U) series), cosmogenic 7Be and technogenic 137Сs was established. The specific activity of 137Cs in the soil on the territory of the Belarusian sector of the 30 km zone of the Ignalina NPP is 2.1–3.5 Bq/kg, the density of surface contamination with this radionuclide is 140–280 Bq/m2. The content of other gamma-emitting technogenic radionuclides, whose activity in the environment is usually monitored to assess the radiation situation, is below the detection limit under these measurement conditions. Application field of research. The data obtained as a result of independent radiation monitoring, characterizing the radiation situation in the zone of influence of the Ignalina NPP, can be the basis for a comparative analysis of the measurement results in the subsequent assessment of the radiation situation in the zone of observation of both the Ignalina and the Belarusian NPP.